Gambaran Karakteristik Ibu yang Mempengaruhi Kejadian Stunting Balita Usia 24-59 Bulan di Puskesmas Talang Banjar Kota Jambi - Reky Marlani; Meri Neherta; Deswita Deswita (Universitas Batanghari Jambi, 2021)
Stunting is a condition of failure to thrive in children under five due to malnutrition for a long time so that children are shorter than normal children their age. This condition is measured by a length or height that is less than minus two standard deviations of the median standard deviation of child growth from the WHO (Kemenkes RI, 2018). This study is an observational study with a descriptive approach to determine the characteristics of mothers that influence the incidence of stunting in toddlers aged 24-59 months in the working area of the Talang Banjar Health Center, Jambi City. The population in this study amounted to 713 and a sample of 256 mothers who had children aged 24-59 months by simple random sampling. The results show that the characteristics of mothers that affect the incidence of stunting in toddlers are mostly from mothers aged 26-35 years (55.4%), work mothers do not work / housewives (90.2%), high maternal education levels (60 ,9%), low socioeconomic (93.5%). It is hoped that nurses can provide health education to mothers with toddlers aged 24-59 months regarding stunting prevention in toddlers so that the prevalence of stunting can decrease.